A systematic comparison of commonly used stoichiometric equations to estimate fat oxidation during exercise in athletes - Peric, R.; Di Pietro, A.; Myers, J.; Nikolovski, Z. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Over the last half-century, different stoichiometric equations for calculating the energy cost of exercise based upon the combustion of mixtures of carbohydrates, fats, and proteins have been proposed and modified. With the means of indirect calorimetry, while measuring oxygen uptake, carbon dioxide production, and urinary urea nitrogen excretion, the contribution of specific substrates to overall energy production can be estimated. However, even with their long history of application, no previous studies have evaluated whether the use of different stoichiometric equations provides similar or distinct maximal fat oxidation rate (MFO) responses and information regarding MFO location (FATmax) in male athletes. METHODS: Twenty healthy male athletes performed graded exercise testing (GXT) cycle ergometry using breath by breath gas analysis to assess fat oxidation and maximal oxygen uptake. Analysis of variance followed by within-equation effects, within-equation factors, and post hoc pairwise comparisons were used to examine within-equation differences. RESULTS: Compared stoichiometric equations demonstrated significant differences in the mean and maximal fat oxidation rates, varying up to nearly 7%. FATmax differences, however, were not noticed. CONCLUSIONS: Our findings suggest that for within-study designs, the equation used appears to be less important, but when inter-study comparisons are planned, caution is in order due to the presence of inter-equation differences.